Pemanfaatan Media Sosial dalam Media Pembelajaran: Tantangan dan Peluang di Pendidikan Sekolah Dasar - Asta Dewi, Lita Argya; Juwita Hanum, Cahaya Zakia A’yunin; Herawati, Yayuk Widyastuti (Jurnal Makkareso, 2024)
Use of social media as a learning medium at SDN 01 Kesamben Village. This article shows that the use of social media as a learning medium has challenges and opportunities that need to be examined carefully. The challenges faced include limited internet access, parents and teachers' concerns about the content consumed by children, and the digital divide which has the potential to create unequal participation and learning experiences. However, the use of social media also opens up opportunities to improve the quality of education, such as providing additional materials, online facilitation, increasing parental involvement, and increasing communication and openness. In order to increase the use of social media in learning at SDN 01 Kesamben Village, efforts are needed to increasing internet access, providing training to teachers and students regarding online security, and building collaboration with related parties to create a more structured and inclusive learning environment. This article shows that the use of social media as a learning medium has challenges and opportunities that need to be studied carefully, so that we can maximize the use of social media while overcoming various obstacles that may arise. Therefore, the use of social media as a learning medium at SDN 01 Kesamben Village needs to be done carefully and structured, so that it can maximize existing opportunities while overcoming various challenges that may arise.